2021
DOI: 10.1155/2021/6652231
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Review of Homocysteine and Pregnancy Complications

Abstract: Homocysteine (Hct) is a substance produced in the metabolism of methionine. It is an essential type of amino acid gained from the daily diet. Methylenetetrahydrofolate reductase (MTHFR) gene mutation is related to elevated total homocysteine (tHct) expressions, in particular, among women with low folate intake. Hyperhomocysteinemia (HHct) is caused by numerous factors, such as genetic defects, lack of folic acid, vitamin B6 and B12 deficiency, hypothyroidism, drugs, aging, and renal dysfunction. Increased Hct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 141 publications
(229 reference statements)
0
64
0
4
Order By: Relevance
“…The association of hyperhomocysteinemia and PE was initially suggested by Decker et al [ 25 , 26 ]. A large number of studies have demonstrated a positive correlation between Hcy and PE and have shown a significant increase in serum Hcy levels in women who develop PE at various stages of pregnancy [ 27 , 28 , 29 ]. In addition, pregnant women complicated by severe PE have shown significantly higher serum Hcy levels than those in the non-severe form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of hyperhomocysteinemia and PE was initially suggested by Decker et al [ 25 , 26 ]. A large number of studies have demonstrated a positive correlation between Hcy and PE and have shown a significant increase in serum Hcy levels in women who develop PE at various stages of pregnancy [ 27 , 28 , 29 ]. In addition, pregnant women complicated by severe PE have shown significantly higher serum Hcy levels than those in the non-severe form.…”
Section: Discussionmentioning
confidence: 99%
“…ADMA has been shown to increase systemic vascular resistance in humans by acting as an endogenous inhibitor of NOS. An elevation of ADMA levels has been widely described in patients with various cardiovascular and metabolic conditions, such as hypercholesterolemia, atherosclerosis, hypertension, chronic heart or kidney failure, diabetes mellitus, and stroke [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated homocysteine levels, derived from the incorrect functioning of the MTHFR enzyme, have also been related to an increased risk of spontaneous abortions [46]. In our series, women with the MTHFR risk allele had a lower frequency of spontaneous pregnancy, i.e., a greater need for assisted fertilization, which may reflect a difficulty in gestation derived from the incorrect functioning of the one-carbon metabolism pathway.…”
Section: Discussionmentioning
confidence: 49%
“…Some 85% of studies showed that women with pre-eclampsia had a higher serum homocysteine concentration than those without pre-eclampsia 138. A high concentration of homocysteine could be associated with a lower level of folate or vitamin B 12 139. Folate requirements are increased in pregnancy due to the rapid division of cells in the fetus and increased urinary losses 140.…”
Section: Resultsmentioning
confidence: 99%